Identification of Lithocholic Acid as a Molecular Glass Host for Room‐Temperature Phosphorescent Materials. Issue 12 (26th September 2022) - Flynn, John J.; Marsh, Zachary M.; Krein, Douglas M.; Wolf, Steven M.; Haley, Joy E.; Vasquez, Erick S.; Cooper, Thomas M.; Godman, Nicholas P.; Grusenmeyer, Tod A.
Abstract: Lithocholic acid was identified as a molecular glass host material for room temperature phosphorescent (RTP) chromophores. Differential scanning calorimetry (DSC) was performed on a series of structurally similar, biologically sourced molecules, including lithocholic acid, β‐estradiol, cholesterol, and β‐sitosterol, in an effort to identify new amorphous molecular glasses independent of plasticizing additives. DSC analysis revealed lithocholic acid and β‐estradiol form stable molecular glasses post thermal processing unlike neat cholesterol and β‐sitosterol. The ability of lithocholic acid and β‐estradiol to stabilize high wt. % loadings of d 10 ‐pyrene and a mixture of d 10 ‐pyrene and an iridium chromophore, bis(2, 4‐difluorophenylpyridinato)‐tetrakis(1‐pyrazolyl)borate iridium(III) (FIr6), was also investigated. All β‐estradiol formulations show β‐estradiol cold crystallization. Optical microscopy and wide angle X‐ray scattering measurements suggest spherulite β‐estradiol crystals form during this process. Finally, time‐resolved luminescence and phosphorescence quantum yield experiments show that the d 10 ‐pyrene RTP lifetime is longer and the d 10 ‐pyrene phosphorescence quantum yield is higher in lithocholic acid molecular glasses than in β‐estradiol molecular glasses. The discrepancy in lifetime and quantum yield values is explained by quantitatively smaller rates of non‐radiative decay from the triplet state of d 10 ‐pyrene in lithocholic acid. Abstract : Lithocholic acid was identified as a molecular glass host material for room temperature phosphorescent (RTP) chromophores. The phosphorescence lifetime and quantum yield of d 10 ‐pyrene are enhanced in lithocholic acid glass relative to β‐estradiol glass due to a reduced rate of non‐radiative decay from the d 10 ‐pyrene triplet state in lithocholic acid.